2001
DOI: 10.1007/s11745-001-0744-2
|View full text |Cite
|
Sign up to set email alerts
|

α‐tocopherol affects the urinary and biliary excretion of 2,7,8‐trimethyl‐2(2′‐carboxyethyl)‐6‐hydroxychroman, γ‐tocopherol metabolite, in rats

Abstract: In this study, we investigated a change in the excretory content of 2,7,8-trimethyl-2(2'-carboxyethyl)-6-hydroxychroman (gamma-CEHC), a gamma-tocopherol (gamma-Toc) metabolite, in rat urine and bile by using a new high-performance liquid chromatography-electrochemical detection (HPLC-ECD) method. In this determination, CEHC [alpha- and gamma-CEHC, where alpha-CEHC = 2,5,7,8-tetramethyl-2(2'-carboxyethyl)-6-hydroxychroman] in the biological specimens were treated with 3 N methanolic HCl to hydrolyze conjugates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 12 publications
1
70
0
Order By: Relevance
“…Tocopherol metabolism, especially that of g-tocopherol or gtocotrienol, and the effects of tocopherols on sodium secretion in rats have been examined by various authors (Clement & Bourre, 1997;Hattori et al, 2000a;Kiyose et al, 2001;Ikeda et al, 2002;Saito et al, 2003). Kiyose et al (2001) investigated the differences of g-CEHC excretion in urine and bile after the oral administration of g-tocopherol or a-þ g-tocopherol to rats, and concluded that a-tocopherol may influence the in vivo metabolism of g-tocopherol to g-CEHC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tocopherol metabolism, especially that of g-tocopherol or gtocotrienol, and the effects of tocopherols on sodium secretion in rats have been examined by various authors (Clement & Bourre, 1997;Hattori et al, 2000a;Kiyose et al, 2001;Ikeda et al, 2002;Saito et al, 2003). Kiyose et al (2001) investigated the differences of g-CEHC excretion in urine and bile after the oral administration of g-tocopherol or a-þ g-tocopherol to rats, and concluded that a-tocopherol may influence the in vivo metabolism of g-tocopherol to g-CEHC.…”
Section: Discussionmentioning
confidence: 99%
“…Kiyose et al (2001) investigated the differences of g-CEHC excretion in urine and bile after the oral administration of g-tocopherol or a-þ g-tocopherol to rats, and concluded that a-tocopherol may influence the in vivo metabolism of g-tocopherol to g-CEHC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stahl investigated the plasma levels of a-CEHC and 2,7,8-trimethyl-2(2 0 -carboxyethyl)-6-hydroxychroman (g-CEHC) in healthy adults taking a-tocopherol, and reported that there was only a slight elevation of g-CEHC (Stahl et al, 1999). Kiyose demonstrated the excretion of g-CEHC after a-and g-tocopherol supplementation in vitamin E deficient rats, and suggested a-tocopherol might affect the metabolism of gtocopherol to g-CEHC (Kiyose et al, 2001). It is also known that tocotrienols, other members of the vitamin E family, are metabolized to CEHCs as well as tocopherols and then excreted in the urine (Lodge et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, the metabolism of vitamin E is indeed very similar in humans and animals. In both, the mechanism of side chain degradation is identical, as is the low degradation rate of a-tocopherol when compared to other forms of vitamin E (reviewed in [15]); all rac-atocopherol is degraded faster than RRR-a-tocopherol [35,74]; c-tocopherol levels are similarly decreased by high dosages of a-tocopherol [36,57] and c-tocopherol metabolism is equally impaired in humans and rats by inhibition of CYP3A [48,31]. In view of these observations, the possibility that a-tocopherol also induces enzymes involved in drug metabolism in humans can not be disregarded, but needs to be investigated, because the system displays species specificity, with particular in respect to the response to inducers.…”
Section: Vitamin E Is Metabolized Like Xenobioticsmentioning
confidence: 99%